2004
DOI: 10.1111/j.1526-4637.2004.04001.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Medical Use and Abuse of Sustained-Release Opioid Analgesics: A Revisit

Abstract: Using this method of analysis, the rates of drug abuse, and resultant morbidity secondary to the use of opioid analgesics, remain low in spite of the increase in medical use of these substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 7 publications
(9 reference statements)
2
45
0
Order By: Relevance
“…3 Moreover, several studies have documented that the (changing) levels of POA available in the population are strongly associated with (changing) levels of POA-related morbidity (for example, emergency department or substance use treatment admissions) and mortality (for example, overdose deaths). 66,67 While current national estimates of NMPOU for the Canadian general adult population are problematic, Ontario-based estimates suggest that this prevalence may be as high as 6.5%; this value would translate into more than 1.5 million Canadians aged 16 years and older. 6,68 Further, surveys have shown that most people with NMPOU obtain their POAs by diversion or nonmedical sourcing from family or friends.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, several studies have documented that the (changing) levels of POA available in the population are strongly associated with (changing) levels of POA-related morbidity (for example, emergency department or substance use treatment admissions) and mortality (for example, overdose deaths). 66,67 While current national estimates of NMPOU for the Canadian general adult population are problematic, Ontario-based estimates suggest that this prevalence may be as high as 6.5%; this value would translate into more than 1.5 million Canadians aged 16 years and older. 6,68 Further, surveys have shown that most people with NMPOU obtain their POAs by diversion or nonmedical sourcing from family or friends.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that OxyContin® is more likely to be used nonmedically by adults than by adolescents (SAMHSA, 2003). Data from the DAWN report suggest significant increases in misuse or abuse of fentanyl, morphine, oxycodone, methadone, and hydrocodone (Novak et al, 2004;SAMHSA, 2003). Our data suggest that American adolescents may be most likely to use hydrocodone products (Vicodin®, Lortab®, Lorcet®, Lorcet Plus®, and hydrocodone), which were used by 52% of all users of non-prescribed pain relievers.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription pain relievers include opioids, such as preparations containing oxycodone (Oxycontin®, Percocet®), hydrocodone (Lortab®, Vicodin®), codeine (Tylenol with codeine®), propoxyphene (Darvon®), methadone (Dolophine®), and hydromorphone (Dilaudid®). Data from the U.S. Drug Abuse Warning Network (DAWN) and the Treatment Episode Data Set (TEDS) show an upward trend in opioid-related admissions to emergency departments (Gilson et al, 2004;Novak et al, 2004; SAMHSA [Substance Abuse and Mental Health Services Administration], 2003) and publicly funded substance abuse treatment facilities (SAMHSA, 2004). For example, an analysis of data from the 1997−2002 DAWN report indicates an increase in opioid-related visits to emergency departments: 642% for fentanyl, 347% for oxycodone, and 342% for hydromorphone (Gilson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in opioid prescribing nationally have been associated with increases in rates of opioid-related serious adverse effects such as overdose mortality (p. 26), prescription pain medication misuse, and opioid-related emergency department visits [20].…”
Section: Serious Adverse Effectsmentioning
confidence: 99%